The Fourth Cataract and beyond : proceedings of the 12th International Conference for Nubian Studies - Anderson, Julie R.; Welsby, Derek A. (British Museum Publications on Egypt and Sudan ;, 2014)
"The 12th International Conference for Nubian Studies was held at the British Museum, London, from 1st-6th August 2010. The conference, held every four years, is the only international gathering of archaeologists and scholars from associated disciplines which considers all aspects of Sudan and southern Egypt's ancient and more recent past. The main sessions, and main papers published herein, were devoted to a consideration of the Merowe Dam Archaeological Salvage Project, its aftermath and impact. Over the previous decade this has been the major focus of archaeological activity on the Middle Nile. The dam is now complete and the reservoir is full drawing a line under the fieldwork component of the project. It was felt timely, therefore, in the interim to obtain an overview of what was found during the many years of intensive work and the first main paper speaker in each session sought to do just that. They were followed by reports on sites, categories of objects and more thematic papers arranged broadly by period. These highlight that, while the focus of archaeological activity still remains the Nile Valley where there is the densest concentration of sites and also where there remains the most concentrated threat to their survival, much work is being undertaken away from the river and in some cases outside its catchment area. The role of the deserts is increasingly being appreciated while the role of the savannah and areas even further south has yet to be given the prominence that it probably deserves"--Page 4 of cover.